14th WCEAM proceedings - Komljenovic, Dragan; Amadi-Echendu, Joe; Crespo Márquez, Adolfo (Switzerland Springer, 2021)
This book gathers selected peer-reviewed papers from the 14th World Congress on Engineering Asset Management (WCEAM), which was held in Singapore on 28–31 July 2019, as well as papers presented during the 1st WCEAMOnline event which focused on the ramifications of Covid-19 on infrastructure systems. This book covers a wide range of topics in engineering asset management, including: asset management services provisioning; servitization; decision-making; asset management systems; industrial Internet of things; and vulnerability and resilience of infrastructure systems. The breadth and depth of these state-of-the-art, comprehensive proceedings make them an excellent resource for asset management practitioners, researchers and academics, as well as undergraduate and postgraduate students.
Electronic reproduction
Keywords: Industrial Management; Building laws; Buildings -- Repair and reconstruction; Buildings -- Maintenance; Operations research; Industrial organization; Electronic books